AKUPRESURE MANDIRI SEBAGAI SALAH SATU ALTERNATIF UNTUK MENJAGA KESEHATAN - Onny Priskila; Alfredo Aldo; Agus Sugiono; Evelyn Purnomo; Ria Cahyani (Randang Tana - Jurnal Pengabdian Masyarakat, 2023)
In 2019, Madiun city received the title red zone covid-19, since then the Madiun city government always take preventive action. Now, covid-19 in indonesia has gone down, but preventive measures must still be taken. One of the preventive actions that can be taken with traditional/complementary medicine is acupressure by ourselves. Acupressure is massage at acupuncture points, also called acupuncture without needles. Some acupressure points for maintaining health is li 4 – hegu, st 36 – zusanli, lv 3 – taichong, and sp 6 – sanyinjiao. Community service activities were carried out on september 18, 2022 in Madiun city. Community service activities were attended by 50 participants. The method of community service activities is education to the community. The most age group participating in counseling was the age of 41-50 years was 40% and the least age > 60 years was 4%. Female participants were 56% and male participants were 44%. Before and after counseling the participants were then given a questionnaire. The questionnaire has 10 questions with a weight of 1. If all questions are answered correctly, the maximum score is 10 and the lowest score is 0. The mean score before counseling was 1,43 and after that 9,05. It can be concluded that the respondents received the educational material very well